EFEKTIVITAS KEPEMIMPINAN SEKTOR PUBLIK KEPALA DESA DI DESA NAGORI PARDOMUAN TONGAH KECAMATAN SILOU KAHEAN KABUPATEN SIMALUNGUN - Pasaribu, Johnson; Panjaitan, Maringan; Saragih, Siska Novita (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Public sector leadership is a very important part of service and is the true essence of leadership as the main part of public service. How public sector leadership can work well so that there is increased community participation is certainly a very important discussion. This research was conducted to see the effectiveness of the village head's leadership in motivating village community participation to improve village infrastructure development. Based on the problems studied, this method and research uses qualitative descriptive research. The results of the research show that the village head of Nagori Pardomuan Tongah has made efforts and roles, such as inviting the community to take part in various village activities with the aim of increasing community participation in development in accordance with with the content, aims and intentions of each development program to be implemented in accordance with his responsibilities and the community as a supporting factor, it is stated that the village head is carrying out his role as less effective. The efforts made by the government in overcoming these obstacles are the village head of Nagori Pardomuan Tongah as a driver and motivator in better village development, the village head should increase motivation to be used as a channel to convey information from each development program , the village head must increase the intensity of implementing development activities with the community for the welfare of the people in the village.